ANALYSIS OF GONIAL ANGLE VARIATIONS IN BATAKNESE INDIVIDUALS BASED ON GENDER AND DENTAL CONDITION USING PANORAMIC RADIOGRAPHY - Manja, Cek Dara; Wahyuni, Siti; Kartika, Dewi; Astrina, Ika; Putri, Asyuni (Universitas Baiturrahmah, 2025)
Introduction: Panoramic radiography provides a comprehensive view of the jaws and is valuable for assessing mandibular morphology, including the gonial angle. Aim: This study aimed to analyze differences in the gonial angle related to dental status and gender within a Bataknese population. Method: An observational analytical study was conducted from June 2022 to July 2023. A total of 120 panoramic radiographs from Bataknese individuals were collected via purposive sampling at the Dental Radiology Installation of the Dental Hospital, Universitas Sumatera Utara, and the Pramita Medan Clinic Laboratory. The sample comprised 60 dentate subjects (control group) and 60 partially edentulous subjects. The gonial angle was measured on each radiograph. Data were analyzed using descriptive statistics and independent samples t-tests, with statistical significance set at p < 0.05. Results: The mean gonial angle in partially edentulous men was 119.942°, compared to 123.367° in women. In the dentate group, the mean angle was 117.497° for men and 121.335° for women. Women had a larger angle than men in both groups. However, no statistically significant difference was found between genders within the partially edentulous group, or between dentate and partially edentulous subjects when analyzed separately by gender. Conclusion: Partial tooth loss was associated with a larger gonial angle in this Bataknese sample, and angles were consistently greater in women. Gender alone did not show a significant effect within the partially edentulous condition.